2018
DOI: 10.1186/s12984-018-0401-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of exercise testing in predicting successful ambulation with a lower extremity prosthesis: a systematic literature review and clinical practice guideline

Abstract: BackgroundGrowing discontent with the k-level system for functional classification of patients with limb loss and movement of healthcare toward evidence-based practice has resulted in the need for alternative forms of functional classification and development of clinical practice guidelines to improve access to quality prosthetic interventions. The purpose of this project was to develop and present a clinical practice recommendation for exercise testing in prosthetic patient care based on the results and synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Situation avoidance leads to activity avoidance and reductions in social and community participation which ultimately results in reduced FIGURE 1 Genium and Genium X3 images, reprinted with permission from Otto Bock Healthcare LP. quality of life (7)(8)(9)(10). However, these reductions may be avoided if features are created to improve the experience of bilateral users because previous research has shown relative fulfilment of rehabilitative potential has a greater impact on mental health and quality of life than the laterality of amputation (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Situation avoidance leads to activity avoidance and reductions in social and community participation which ultimately results in reduced FIGURE 1 Genium and Genium X3 images, reprinted with permission from Otto Bock Healthcare LP. quality of life (7)(8)(9)(10). However, these reductions may be avoided if features are created to improve the experience of bilateral users because previous research has shown relative fulfilment of rehabilitative potential has a greater impact on mental health and quality of life than the laterality of amputation (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Before starting exercise training, a valid, reliable and safe physical exercise test especially with regard to cardiovascular risks is required to design exercise training programs. Additionally, outcomes of exercise tests should help to predict successful ambulation with a prosthesis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe diabetic management costs are various: from 1.305 €/year in Spain, to 3.576 €/year in Germany. In Italy the main cost is about 2.990 €/year, for a national expenditure of 5 billion euros every year [4][5][6]. 60% of this expenditure is caused by in-hospital care, other for ambulatorial cares and drugs.…”
Section: Introductionmentioning
confidence: 99%